Differential associations of homelessness with emergency department visits and hospitalizations by race, ethnicity, and gender. (30th May 2022) - Yue, Dahai; Pourat, Nadereh; Essien, Elsie A.; Chen, Xiao; Zhou, Weihao; O'Masta, Brenna
Abstract: Objective: To investigate the differential associations of homelessness with emergency department (ED) visits and hospitalizations by race, ethnicity, and gender. Data Sources: California Medicaid enrollment and claims. Study Design: We identified beneficiaries experiencing homelessness (BEH) and those who did not (NBEH) using diagnosis and place of service codes and residential addresses. Outcomes include four ED visit measures and four hospitalization measures. We compared the use of these services by BEH to NBEH overall and by race, ethnicity, and gender groups in regression models controlling for covariates. Data Collection: We used a sample of Medicaid beneficiaries who met eligibility criteria for a California Medicaid demonstration program in 2017 and 2018 but were not enrolled in the program. We identified 473, 069 BEH, and the rest (1, 948, 422) were considered NBEH. We used the 2018 data for utilization analyses and most covariates. We constructed lagged measures of health conditions using 2017 data. Principal Findings: We found that homelessness was significantly associated with 0.34 more ED visits ( p  < 0.01) and a higher likelihood of frequent ED visits (2.77 percentage points [pp], p  < 0.01), any ED visits due to mental health conditions (0.79 pp, p  < 0.01), and any ED visits due to substance use disorders (1.47 pp, p  < 0.01). Experiencing homelessness was also significantly associated with 0.03 more hospitalizations ( p  < 0.01), a higher likelihood of frequent hospitalizations (0.68 pp, p  < 0.01) and high frequent hospitalizations (0.28 pp, p  < 0.01), and a longer length of stay (0.53 days, p  < 0.01). We found a larger association for American Indian and Alaska Native, Black, Native Hawaii or Pacific Islander, and White populations than that for Asian and Hispanic populations. The associations are larger for males than females. Conclusions: Our findings identified distinct utilization patterns by race, ethnicity, and gender. They indicated the need for developing race, ethnicity, and gender‐specific strategies to reduce ED visits and hospitalizations of BEH.